Interval Criteria for Oscillation of Damped Second-order Nonlinear Impulsive Differential Equation with Variable Delay - Muthulakshmi, V.; Manjuram, R. (Discontinuity, Nonlinearity, and Complexity, 2026)
This paper is devoted to the study of the oscillatory behavior of damped second order nonlinear impulsive differential equations with variable delay. The results obtained here extend and complement to some known results in the literature.